Peroxidation of n-3 and n-6 polyunsaturated fatty acids in the acidic tumor environment leads to ferroptosis-mediated anticancer effects - Dierge, Emeline; Debock, Elena; Guilbaud, Céline; Corbet, Cyril; Mignolet, Eric; Mignard, Louise; Bastien, Estelle; Dessy, Chantal; Larondelle, Yvan; Feron, Olivier (Cell metabolism, 2021)
Tumor acidosis promotes disease progression through a stimulation of fatty acid (FA) metabolism in cancer cells. Instead of blocking the use of FAs by acidic cancer cells, we examined whether excess uptake of specific FAs could lead to antitumor effects. We found that n-3 but also remarkably n-6 polyunsaturated FA (PUFA) selectively induced ferroptosis in cancer cells under ambient acidosis. Upon exceeding buffering capacity of triglyceride storage into lipid droplets, n-3 and n-6 PUFA peroxidation led to cytotoxic effects in proportion to the number of double bonds and even more so in the presence of diacylglycerol acyltransferase inhibitors (DGATi). Finally, an n-3 long-chain PUFA-rich diet significantly delayed mouse tumor growth when compared with a monounsaturated FA-rich diet, an effect further accentuated by administration of DGATi or ferroptosis inducers. These data point out dietary PUFA as a selective adjuvant antitumor modality that may efficiently complement pharmacological approaches. [Display omitted] •n-3 and n-6 PUFAs preferentially accumulate in lipid droplets of acidic cancer cells•Excess LC-PUFAs undergo peroxidation and induce ferroptosis in acidic cancer cells•DGAT inhibitors prevent the formation of lipid droplets and promote ferroptosis•DGATi enhance the tumor growth inhibitory effects of dietary n-3 LC-PUFAs in mice Tumor acidosis is associated with the metabolic use of fatty acids. Dierge et al. describe that in acidic cancer cells, n-3 and n-6 LC-PUFAs that exceed lipid droplet storage capacity undergo peroxidation and induce ferroptosis. Antitumor effects of dietary n-3 LC-PUFAs are further increased upon administration of DGAT inhibitors.